Towards effective planning and implementation of development initiatives at the local level in Capricorn District Municipality, Limpopo Province, South Africa - Asha, Aklilu Admassu (My University, 2014)
In South Africa, various studies have indicated that achieving developmental mandates by local authorities is one of the biggest challenges largely due to poor planning and implementation. For instance, many local municipalities had performed inadequately in relation to their functionalities in planning and implementation of various IDP initiatives in Limpopo. The purpose of this research was to assess how local municipalities can further enhance their effectiveness in planning and implementation of development initiatives at the local level in Capricorn District Municipality, Limpopo Province South Africa. The methodology of this study was largely a qualitative case study and the quantitative approach was also used to augment the qualitative findings. The study was undertaken in three local municipalities such as Polokwane, Lepelle-Nkumpi and Agnang by engaging various IDP stakeholders including local government officers and the community representatives. The findings indicated that the local municipalities in the study area have not successfully played their role in local development. The basic service delivery was largely inadequate, the role in poverty alleviation was insufficient and community participation remains a serious concern at the local level. The finding reveals, inter alia, that the decision making process is limited, delayed and inconsistent; the institutional capacity was largely inadequate; limited understanding of IDP; limited stakeholder’s commitment; limited responsiveness to the local needs and priorities; and challenges in inclusive and wider involvement at ward and village levels. Furthermore, it was discovered that the local municipalities has not effectively addressed the planning and implementation of IDPs. The finding shows, inter alia, that tendency of top-down and technocratic planning; a concern over IDP on whether iv it reflects people’s needs and aspirations; lack of mobilisation of local resources; difficulty in integration and coordination; IDP projects implementation is slow, lacks sustainability and limited impact; and poor monitoring and evaluation of IDPs due to limited participation, lack of capacity and deficiencies in processes and procedures. Based on the findings, this research proposed the necessary strategic interventions and a framework for improving the effectiveness of the existing approach to planning and implementation of IDPs in the local municipalities. Therefore, it is recommended that local municipalities should promote their development role through strengthening the decision making process, institutional capacity, commitment, responsiveness and inclusive approach to local development. It is also recommended that local municipalities should emphasize more on people’s needs and priorities and encourages ward based planning approach to improve the planning process of IDPs. Likewise, local municipalities should strengthen their IDP implementation through mobilisation of local resources, better integration and coordination, improved project implementation, monitoring and evaluation. Furthermore, the proposed framework for strengthening the planning and implementation of IDPs be implemented, evaluated and integrated into the current IDP process of the local municipalities. Key concepts: development, decentralised development, local government, development role of local government, integrated development planning, Integrated Development Plans (IDPs), development planning, and development implementation.
Thesis (Ph.D. (Development Studies)) --University of Limpopo, 2014
Keywords: Integrated Development Plans; Local government; Municipal government; Local government -- South Africa -- Limpopo.; Municipal government -- South Africa -- Limpopo.; Rural development -- South Africa -- Limpopo.; Community development.